Fase sexual de los helechos Odontosoria schlechtendalii y Odontosoria scandens (Dennstaedtiaceae) - Granados, Beatriz (2003)
The results of morphogenesis studies of the sexual phase of Odontosoria schlechtendalii and O. scandens are presented in this paper. In O. schlechtendalii and O. scandens the spores are triletes, non-chlorophyllous, and germinación is of the Vittaria-type, devoid of perine, the exine is smoth and sometimes coarsely ridged to reticulate. The development pattern is of the Adiantum-type. The adult gametophyte is cordate-spathulate, with probable presence of anteridiogen in O. schlechtendalii, both species are glabrous. Sex organs are of the common type of the leptosporangiate ferns. The first leaves appeared after 56-92 days of culture, with petiole and plate divide narrow, trichomes bifurcate and stomate anomocytic.